2011
DOI: 10.1002/adsc.201100622
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene‐Catalyzed Enantioselective Annulation of Bromoenal and 1,3‐Dicarbonyl Compounds

Abstract: Highly enantioselective [3 + 3] annulation reactions of bromoenals and 1,3-dicarbonyl compounds are reported. In addition, both enantiomers of the resultant dihydropyranone could be easily obtained by choosing N-heterocyclic carbenes (NHCs) with the same stereocenter but different substituents under the optimized reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(77 citation statements)
references
References 83 publications
2
74
0
1
Order By: Relevance
“…Contemporaneously, Lupton has reported the related NHC-catalyzed annulation of α,β -unsaturated acyl fluorides and enol silanes 28 or unsaturated enol ester 29 using achiral imidazolium-derived NHCs – a process also thought to occur via a related unsaturated acyl azolium. Xiao, 30, 31 Studer, 32, 33 You, 34 and Ye 35 also reported similar annulation cascades. Lupton 36 has recently reported an elegant NHC-catalyzed formal [4+2] cycloaddition that proceeds via the catalytic generation of α,β -unsaturated acyl azolium.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Contemporaneously, Lupton has reported the related NHC-catalyzed annulation of α,β -unsaturated acyl fluorides and enol silanes 28 or unsaturated enol ester 29 using achiral imidazolium-derived NHCs – a process also thought to occur via a related unsaturated acyl azolium. Xiao, 30, 31 Studer, 32, 33 You, 34 and Ye 35 also reported similar annulation cascades. Lupton 36 has recently reported an elegant NHC-catalyzed formal [4+2] cycloaddition that proceeds via the catalytic generation of α,β -unsaturated acyl azolium.…”
Section: Introductionmentioning
confidence: 69%
“…Although the conversion was low, the formation of the expected product in respectable enantioselectivity demonstrated that the α,β -unsaturated acyl azolium is not precluded from the possibility of undergoing 1,4 addition with suitable nucleophile. 80 The related annulations of α,β -unsaturated acyl azoliums and enols or enolates 2835 have all invoked this mechanistic paradigm.…”
Section: Mechanistic Considerationmentioning
confidence: 99%
“…20 Michael addition of aldimine 2 via its enamine tautomer to -unsaturated acyl azolium III generates adduct IV, which then undergoes intramolecular cyclization via its enamine to afford final cycloadduct 3 and regenerates the NHC catalyst. The addition of NHC catalyst to bromoenal 1 induces the formation of Breslow intermediate I, which is tautomerized to bromoketone II, The leaving of the bromide generates the key -unsaturated acyl azolium intermediate III.…”
mentioning
confidence: 99%
“…The position and electronic properties of substituents on the aromatic ring of aryl-substituted 2-bromoenals did not signicantly affect reaction efficiency (entries [11][12][13][14][15][16][17][18][19]. 2-bromoenals 3.…”
mentioning
confidence: 99%